A dynamic test methodology for analyzing the strain-rate effect on the longitudinal compressive behavior of fiber-reinforced composites. (15th November 2017) - Ploeckl, Marina; Kuhn, Peter; Grosser, Jürgen; Wolfahrt, Markus; Koerber, Hannes
Abstract: This paper presents an experimental study of the strain-rate effect on the longitudinal compressive strength of UD carbon-epoxy IM7/8552 and UD carbon-fiber-reinforced polyamide-6. A test setup for dynamic measurements using a split-Hopkinson pressure bar was developed to achieve valid compressive failure in the specimen's free gauge section. The setup presented improves on the dynamic compression fixture developed in an earlier study [Koerber and Camanho, Composites Part A 2011;42]. Greater static and dynamic longitudinal compressive strength values of an IM7/8552 UD laminate were achieved than in this earlier study. The absolute values obtained for the UD laminate were nonetheless still thought to underestimate the actual material property. Realistic dynamic longitudinal compressive strength values were achieved for the first time by testing a multi-directional laminate, which yielded the desired valid failure mode, then calculating the longitudinal compressive strength of the embedded 0°-UD ply using a procedure based on classical laminate theory. For IM7/8552, a dynamic compressive strength of 2008 MPa at 100 s - 1 was measured compared to a static value of 1454 MPa. This corresponds to a strength increase of 40% confirming the quantitative strain-rate effect observed in the earlier study. A 60% strength increase was measured for UD carbon-fiber-reinforced polyamide-6 at the same strain-rate levels.